The cooling performance of a natural draft dry cooling tower under crosswind and an enclosure approach to cooling efficiency enhancement. (15th January 2017) - Wang, Weiliang; Zhang, Hai; Liu, Pei; Li, Zheng; Lv, Junfu; Ni, Weidou
Highlights: The cooling performance of a NDDCT under crosswind condition was investigated. The resistance of radiators was simulated using a viscous force based equation. A gentle breeze or stronger wind may influence the cooling performance of a NDDCT. Vortices and circumferential non-uniformity are the main degrading factors. An enclosure approach to cooling efficiency enhancement is found to be effective. Abstract: Cooling performance of a natural draft dry cooling tower degrades in presence of crosswind. Upon an in service natural draft dry cooling tower of a 660 MW unit in China, a computational fluid dynamics approach with validation is adopted to investigate the cooling performance at various wind speeds. The first order viscous force based resistance mechanism is used in simulating the air flow resistance for the radiators. Numerical results confirm previous findings that the cooling performance of the natural draft dry cooling tower degrades with the increment of wind velocity when wind velocity is higher than 4 m/s, but the performance reduction is relatively less. The circumferential non-uniform ventilation and the vortices inside the tower contribute the most to the degrading of the cooling performance when crosswind is present. To enhance the overall cooling performance, an enclosure with an opening at the windward side is proposed to increase the pressure level outside the side and back radiators. Numerical results show that such an enclosure could enhance the cooling performance at all investigated wind speeds, with 36% increase of the ventilation rate and about 7 °C decrement of the cycling water temperature at 20 m/s.